Functional finishing and coloration of textiles with nanomaterials. (21st May 2018) - Riaz, Shagufta; Ashraf, Munir; Hussain, Tanveer; Hussain, Muhammad Tahir; Rehman, Abdur; Javid, Amjed; Iqbal, Kashif; Basit, Abdul; Aziz, Humera
Abstract : Global demand for functional textiles is continually increasing for both conventional as well as advanced technical applications. Nanomaterials have the potential to transform the textile industry by imparting multifunctional properties such as physical, chemical and biological self‐cleaning, ultraviolet (UV) protection, wrinkle resistance and coloration to textiles without compromising the inherent characteristics of the substrate. This review highlights some of the major applications of nanomaterials to textile substrates to obtain different functional properties. Possible side effects of the nanomaterials on textiles are also reviewed, along with potential hazards to humans and the environment.